Pedevelopment of Problem-Based Learning (PBL) Based E-LKPD on Respiratory System Materials to Improve Students' Critical Thinking Skills - Ahmad Farkhan Arrofiqi; Raharjo; Elma Sakinatus Sajidah (CV. Edujavare Publishing, 2026)
Critical thinking skills are higher-order thinking skills that are essential to be developed in biology learning. This development research aimed to produce a Problem-Based Learning (PBL)-based electronic student worksheet (E-LKPD) on the respiratory system topic to improve students’ critical thinking skills, which is feasible in terms of validity, practicality, and effectiveness. The development of the E-LKPD employed the 4D model consisting of define, design, develop, and disseminate stages. The product trial was conducted on 36 eleventh-grade students of SMAN 14 Surabaya. The parameters measured in this study included validity assessed by experts, practicality based on the implementation of learning activities and students’ responses, and effectiveness based on the improvement of students’ critical thinking skills from pretest and post-test results. The data were analyzed using descriptive quantitative methods. The results showed that the developed E-LKPD obtained a validity score of 98.75%, categorized as very valid. The practicality of the E-LKPD based on the implementation of learning activities reached 98.5%, while students’ responses reached 97.8%, both categorized as very practical. The effectiveness of the E-LKPD was indicated by the improvement of students’ critical thinking skills with an N-Gain score of 0.74 which falls into the moderate category.